Hydric balance in clinical practice nursing in coronary unit - Sherida Karanini Paz de Oliveira; Maria Vilaní Cavalcante Guedes; Francisca Elisângela Teixeira Lima (Rev Rene)
As they perform and record data on the water balance, nurses must be aware of the results, to interfere whenever necessary. The objective of this study was to understand the significance of hydric balance for nurses working in an intensive care coronary unit and to verify the use of results from hydric balance in nursing care. It is a descriptive study, conducted in a public hospital, located in Fortaleza. The research included the participation of eight nurses who had volunteered for the study. To obtain the data, we used a semi structured interview. The themes identified were: hydric balance concept, realization of hydric balance and use of the results of hydric balance in the clinical practice of nursing. It was concluded that most nurses have a concept of hydric balance, even deprived of complexity and they try to apply the results in their daily practice.